2015
DOI: 10.17221/8559-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rabbit-origin enterocin-producing probiotic strain Enterococcus faecium CCM7420 application on growth performance and gut morphometry in rabbits

Abstract: ABSTRACT:The interactions between probiotic bacteria and the immune system in animals are known, but particularly in rabbits have not been sufficiently documented. Therefore the present study deals with the effect of the enterocin-producing probiotic strain Enterococcus faecium CCM7420 on the growth performance and jejunal morphometry in rabbits. Forty-eight weaned rabbits of male sex (NZB breed) at 5 weeks of age were randomly divided into experimental (EF) and control group (CG) with 24 rabbits in each group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
11
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 8 publications
6
11
0
1
Order By: Relevance
“…On the other hand, there is new potential for morphometry influence using bacteriocins. Throughout our EntM and sage administration, all the tested morphological parameters in the jejunum were increased compared to control data (except CD, which were decreased), with the highest values in group E. These results are in accordance with those obtained during morphological parameter testing in the rabbit jejunum and ileum using probiotics and prebiotics [55,56], but they are also contrary to nisin application in rabbits, when the jejunal morphology was not influenced [13]. The improved morphometry parameters during additive application suggest better functionality of the intestinal mucosa, more effective intestinal immunity through IgA production, enlargement of the surface area capable of greater absorption of available nutrients, leading to better health status and meat quality, and higher weight gains in rabbits.…”
Section: Discussionsupporting
confidence: 87%
“…On the other hand, there is new potential for morphometry influence using bacteriocins. Throughout our EntM and sage administration, all the tested morphological parameters in the jejunum were increased compared to control data (except CD, which were decreased), with the highest values in group E. These results are in accordance with those obtained during morphological parameter testing in the rabbit jejunum and ileum using probiotics and prebiotics [55,56], but they are also contrary to nisin application in rabbits, when the jejunal morphology was not influenced [13]. The improved morphometry parameters during additive application suggest better functionality of the intestinal mucosa, more effective intestinal immunity through IgA production, enlargement of the surface area capable of greater absorption of available nutrients, leading to better health status and meat quality, and higher weight gains in rabbits.…”
Section: Discussionsupporting
confidence: 87%
“…Lam Phuoc and Jamikorn (2017) reported that the dietary supplementation with L. acidophilus and B. subtilisplus improved body weight of rabbits than the control rabbits. Pogány Simonová et al (2015) found that daily gain of rabbits fed the diet supplemented with Enterococcus faecium CCM7420 strain was higher than their control counterparts. …”
Section: Live Body Weightmentioning
confidence: 99%
“…Chandra et al (2014) attributed the improvement in growth performance in response to feeding the probiotic-supplemented diets to improved nutrient digestibility and absorption in the ileum. Pogány Simonová et al (2015) reported that the administration of Enterococcus faecium CCM7420 strain to the rabbits altered their growth performance; these changes may influence the gut function and improve the nutrient uptake. Ogunsipe (2014) found that lowest cost of feed /weight gain for rabbits was recorded when rabbits were fed enzyme supplemented-based diet.…”
Section: Protein and Energy Utilization Performance Index And Econommentioning
confidence: 99%
“…In addition, probiotic can improve the condition of digestive canal that is short of digestive enzymes (Wang et al, 2008). Also, probiotic may improve weight gain due to better utilization of feed and larger absorption surface in the gut and also may positively influence the health status via enhancing the gut health in rabbits (Pogány et al, 2015).…”
Section: Feed Restriction System (Fr)mentioning
confidence: 99%